The endurance athletes heart: acute stress and chronic adaptation. (24th October 2012) - George, Keith; Whyte, Greg P; Green, Danny J; Oxborough, David; Shave, Rob E; Gaze, David; Somauroo, John
Abstract : The impact of endurance exercise training on the heart has received significant research and clinical attention for well over a century. Despite this, many issues remain controversial and clinical interpretation can be complex of biomarkers of cardiomyocyte insult. This review assesses the current state of knowledge related to two areas of research where problems with clinical decision making may arise: (1) the impact of chronic endurance exercise training on cardiac structure, function and electrical activity to the point where the athletic heart phenotype may be similar to the expression of some cardiac pathologies (a diagnostic dilemma referred to as the 'grey-zone') and (2) the impact of acute bouts of prolonged exercise on cardiac function and the presentation of biomarkers and cardiomyocyte insult in the circulatory system. The combination of acute endurance exercise stress on the heart and prolonged periods of training are considered together in the final section.